Kedudukan Harta Waris dalam Kaitannya dengan Program Pengungkapan Sukarela dalam Perpajakan - Mustika Prabaningrum Kusumawati; Ahmad Khairun Hamrany; Ari Nur Rahman (Jurnal Hukum IUS QUIA IUSTUM, 2023)
The government issued a policy of Voluntary Disclosure Program bearing a final tax rate which is later known as PAS FINAL to avoid the imposition of 200% administrative sanctions if discovered by auditors. However, socialization is not carried out sustainably and optimally. The government optimizes fiscal revenues through the Voluntary Disclosure Program (PPS) through Law Number 7 of 2021 and PMK No.196/PMK.03/2021. The formulation of the problem is how are taxpayers in various regions interested to participate in the Voluntary Disclosure Program (PPS) and what is the juridical review of undivided and divided inheritance owned by taxpayers in the Voluntary Disclosure Program (PPS)? According to the author, the level of interest to participate in PPS is still low, because there are still many taxpayers who have never heard of and do not understand about the said PPS. This condition is underscored by the high number of taxpayers who choose not to take part in PPS even though they know and understand PPS. Apart from that, there are a high number of taxpayers who do not understand the tax treatment of inherited assets in the PPS program. Taxpayers' high level of misunderstanding of the tax treatment of inherited assets can reduce their interest in participating in PPS. From a juridical aspect, inherited assets that should be included in PPS are those that have the status of inherited assets that have not been divided but generate income. With the transfer of tax obligations to the heirs after the heir dies, the Taxpayer's heirs should be the ones to take part in the voluntary disclosure program for income originating from undivided inheritance.Keywords: Inheritance; Taxpayer, Voluntary Disclosure Program (PPS) AbstrakPemerintah mengeluarkan kebijakan Program Pengungkapan Sukarela dengan tarif pajak final yang dikenal dengan PAS FINAL untuk menghindari pengenaan sanksi administrasi 200% apabila ditemukan oleh pemeriksa. Namun sosialisasi tidak dilakukan secara berkelanjutan dan maksimal. Pemerintah melakukan optimalisasi penerimaan fiskal melalui Program Pengungkapan Sukarela (PPS) melalui Undang-Undang Nomor 7 Tahun 2021 dan PMK No.196/PMK.03/2021. Rumusan masalahnya adalah bagaimana Wajib Pajak di berbagai daerah tertarik mengikuti Program Pengungkapan Sukarela (PPS) dan bagaimana tinjauan yuridis terhadap harta warisan belum terbagi dan telah terbagi yang dimiliki Wajib Pajak dalam Program Pengungkapan Sukarela (PPS)? Tingkat ketertarikan mengikuti PPS menurut penulis masih rendah, dikarenakan masih banyaknya Wajib Pajak yang belum pernah mendengar serta belum paham tentang PPS. Kondisi tersebut dipertegas dengan tingginya Wajib Pajak yang memilih tidak mengikuti PPS meskipun pernah mengetahui dan memahami PPS. Selain itu tingginya Wajib Pajak yang tidak memahami perlakuan pajak atas harta warisan pada program PPS. Tingginya ketidakpahaman Wajib Pajak terhadap perlakuan pajak atas harta warisan dapat mengurangi ketertarikan dalam mengikuti PPS. Secara aspek yuridis harta warisan yang seharusnya diikutkan dalam PPS adalah yang berstatus harta waris yang belum terbagi tetapi menghasilkan pendapatan. Dengan telah beralihnya kewajiban perpajakan kepada ahli waris setelah pewaris tersebut meninggal, seharusnya Wajib Pajak Ahli Waris tersebut yang mengikuti program pengungkapan sukarela atas pendapatan yang berasal dari harta waris yang belum terbagi.Kata Kunci: Program Pengungkapan Sukarela (PPS); Wajib Pajak; Warisan.